FAKTOR RESIKO FRAUD TERHADAP PELAKSANAAN FRAUDULENT FINANCIAL REPORTING (BERDASARKAN PENDEKATAN CROWN’S FRAUD PENTAGON THEORY) - Sasongko, Noer; Wijayantika, Sangrah Fitriana (Universitas Muhammadiyah Surakarta, 2019)
The purpose of this study was to analyze fraud risk factors on the implementation of fraudulent financial reporting, based on crown’s fraud pentagon theory. There are 8 variables in this study, which are thought to influence fraud. This research consists of Pressure (financial stability, financial target, external pressure), opportunity (nature of industry), rationalization (auditor turnover), capability (change of directors), arrogance (frequent member of CEO picture, CEO duality). The population of this study is a manufacturing company listed on the Indonesia Stock Exchange (BEI) for the period 2014-2016. The research sample was taken by purposive sampling. Data analysis using logistic regression. The results showed that the change of directors affected Fraudulent Financial Reporting, while financial stability, financial targets, external pressure, nature of industry, auditor turnover, frequent member of CEO picture, CEO duality had no effect on Fraudulent Financial Reporting. Keywords: Fraudulent Financial Reporting, Pentagon Fraud, dan Fraud